KOMPLEKSITAS AKUNTANSI PERUSAHAAN, SPESIALIS INDUSTRI AUDITOR, EFEKTIVITAS KOMITE AUDIT, DAN FAKTOR LAIN TERHADAP AUDIT REPORT LAG - BUDIARTO BUDIARTO; FERRY SUHARDJO (E-Jurnal Akuntansi TSM, 2021)
This study aims to obtain empirical evidence and to analyze the factors that affect the audit report lag of non-financial companies on the IDX. The independent variables tested in this study were the effectiveness audit committee, the complexity accounting firm, profitability, auditor reputation, audit tenure, specialist industry auditors, solvency, and firm size. The sample of this research is 398 non-financial company data by taking the period 2017 - 2019. This research uses purposive sampling and this research uses multiple regression analysis. The results of this study indicate that the effectiveness of the audit committee, the complexity of company accounting, profitability, audit tenure, solvency, and firm size have an influence on the audit report lag. The reputation of auditors and specialist industry auditors has no effect on the audit report lag